A Cross-Sectional Study of the Association between Overnight Call and Irritable Bowel Syndrome in Medical Students - Malcolm Wells; Lee Roth; Morgan McWilliam; Kim Thompson; Nilesh Chande (Canadian Journal of Gastroenterology)
BACKGROUND: Shift work has been associated with irritable bowel syndrome (IBS), which includes gastrointestinal symptoms such as abdominal pain, constipation and diarrhea. Overnight call shifts also lead to a disruption of the endogenous circadian rhythm.